Age-adjusted charlson comorbidity index and 30-day morbidity in pelvic surgeries - Dessai, Sampada B.; Fasal, R.; Dipin, J.; Adarsh, D.; Balasubramanian, Satheesan (South Asian Journal of Cancer, 2018)
Introduction: Charlson comorbidity index (CCI) is a validated tool enabling clinicians for prediction of adverse events posttherapy. In this study, we planned to estimate the predictive value of age-adjusted CCI (ACCI) in assessing the perioperative complication in oncological patients undergoing major pelvic surgeries. Methods: This was a single arm, prospective, observational study, in which adult patients with pelvic malignancies undergoing pelvic surgeries were selected. The relationship between the ACCI and Grade 3–5 adverse events were tested using Fisher's test. Results: The rate of Grade 3–5 adverse event rate was 16.7% (11 patients, n = 66). Among the whole cohort, 11 patients (16.7%) had high score on ACCI. The rate of Grade 3–5 adverse events was higher in the cohort of patients with high ACCI score (45.5% vs. 10.9%, P = 0.014). The sensitivity, specificity and negative and positive predictive values were 45.5%, 89.1%, 89.1%, and 45.5%, respectively. Conclusion: ACCI can predict for postsurgical adverse events. It has a high negative predictive value for nonoccurrence of adverse events.
Keywords: Adverse events; age adjusted Charlson comorbidity index; Charlson comorbidity index; complications; pelvic; surgeries